Gibberellic Acid (GA3) and Potassium Nitrate (KNO3): The Influence and Interaction inThe Senescence Process in White Rosa Sp. - Nur Jannah Cortesa; Martha Lulus Lande; Zulkifli Zulkifli; Tundjung Tripeni Handayani (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
The purpose of this study was to find out whether the combination of KNO3 and GA3 solutions were more effective than a single solution of KNO3 or GA3 in keeping the freshness of cut flowers. The research was conducted in Botanical Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences University of Lampung from November to December 2017. The experiment was conducted in 2 x 3 factorial experiment with factor A is GA3 solution with 3 concentration level: 0% w/v, 25% w/v, and 0.5% w/v. Factor B is KNO3 solution with 2 concentration levels: 0% w/v and 5% w/v. The parameters of this study were fresh weight, dry weight, relative water content, total chlorophyll content, total chlorophyll of leaves, and total carbohydrate content of rose cut flowers. Measurements were made 7 days after the immersion of cut flowers in KNO3 or GA3 solution, and mixed both. Homogeneity of variance and analysis of variance is determined at confidence level 5%. KNO3 simple effect at every level of GA3 concentration is determined by the F test at 5%. The results showed that there was no interaction between GA3 and KNO3 to fresh weight, dry weight, relative water content and chlorophyll content a, b and total white roses, but KNO3 reduced fresh weight of cut flowers by 48.15% and dry weight 58.60%. KNO3 increased the relative water content of white rose flowers by 6.85%. The results of the study concluded that the combination of GA3 and KNO3 is not effective to keep the freshness of white rose flowers cut.